Epidemiological analysis of the incidence and resolution of the infection by the human papillomavirus in women undergoing a retrospective follow-up study (2013)
There are few longitudinal studies in Colombia that cover people from different parts of the country to allow understanding the infection dynamics by Human Papilloma Virus (HPV). A representative sample of 1433 women from three Colombian cities aged 18-60 years which were visited every 6 ± 2 months during two years, were submitted to the Papanicolau and reaction Polymerase chain (pcr) tests. Infection incidence was 2.49 /1000 women/day (CI 95%, 2.25-2.75), the incidence rate for lesion was 0.043 lesion/1000 women/day (CI 95%, 0.021-0.086), while for infection clearance the rate was 2.47 infection clearance/1000 women/day (CI 95%, 2.25-2.71). A women´s subgroup who reported having lesions on the first visit, had a rate of 3.92 lesion-regressions/1000 women/day (CI 95%, 2.97-5.17). From a group of 619 women with infection, 27% reported a persistent infection and only 10% of 55 women with cervical lesion kept this condition. Data showed that incidence and infection resolution was frequent, while the epidemiological study of lesions would require a greater number of women and a cohort of longer duration.